2010
DOI: 10.1002/rcm.4684
|View full text |Cite
|
Sign up to set email alerts
|

Error propagation in normalization of stable isotope data: a Monte Carlo analysis

Abstract: A higher analytical precision of a stable isotope ratio mass spectrometer does not automatically guarantee accurate determination of the true isotope composition (delta-value) of samples, since estimates of true delta-values are obtained from the normalization of raw isotope data. We performed both Monte Carlo simulations and laboratory experiments to investigate aspects of error propagation during the normalization of carbon stable isotope data. We found that increasing both the number of different reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 13 publications
(35 reference statements)
1
56
0
Order By: Relevance
“…The calculated d 13 C values of other international standards, including IAEA-CH-6, IAEA-CH-3, and USGS40, were well fitted to the literature values within 0.04%, although USGS41 was slightly (0.19%) lower than the accepted value. This is consistent with Skrzypek et al (2010), who have shown that a higher mean error was observed outside the range bracketed by the d values of the anchor standards (L-SVEC and NBS19). Table 2 In the studies of limnology and ecology, stable isotope ratios are often used for investigating nutrient dynamics and food-web structure.…”
Section: Methodssupporting
confidence: 90%
“…The calculated d 13 C values of other international standards, including IAEA-CH-6, IAEA-CH-3, and USGS40, were well fitted to the literature values within 0.04%, although USGS41 was slightly (0.19%) lower than the accepted value. This is consistent with Skrzypek et al (2010), who have shown that a higher mean error was observed outside the range bracketed by the d values of the anchor standards (L-SVEC and NBS19). Table 2 In the studies of limnology and ecology, stable isotope ratios are often used for investigating nutrient dynamics and food-web structure.…”
Section: Methodssupporting
confidence: 90%
“…Multipoint normalization was used in order to reduce raw values to the international scale [Paul et al, 2007]. Error propagation for stable isotope data was performed as described by Skrzypek et al [2010]. The external error of analyses (1 standard deviation) was 0.15‰ for δ 13 C and 0.20‰ for δ 15 N. Nitrogen assimilation and C fixation rates ( ρ in nmol N or C L À1 h À1 ) were calculated following Dugdale and Goering [1967] and Knap et al [1996].…”
Section: 1002/2015gb005194mentioning
confidence: 99%
“…Back in the laboratory on land, filters were acidified and dried overnight at 60°C. Analysis of the 15 N 2 incorporation into the particulate organic matter (POM) was carried out using a continuous flow sys-tem consisting of a Sercon 20-22 mass spectrometer connected with an ANCA (Sercon) at the West Australian Biogeochemistry Centre at the University of Western Australia (Paul et al 2007, Skrzypek et al 2010. Final 15 N atom enrichment was calculated assuming complete dissolution of the gas bubble.…”
Section: N 2 Fixation Ratesmentioning
confidence: 99%
“…Multipoint normalization was used in order to reduce raw values to the international scale (Paul et al 2007). Standard selection for δ 13 C was as described by Skrzypek et al (2010).…”
mentioning
confidence: 99%